1996
DOI: 10.1007/s004390050304
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite polymorphism of the α 1 -antichymotrypsin gene locus associated with sporadic Alzheimer's disease

Abstract: A variant of the apolipoprotein E gene, APOE*4, is associated with both sporadic Alzheimer's disease (AD) and a subset of familial AD and this association is stronger with early as opposed to late onset AD. Both APOE*4 and alpha 1-antichymotrypsin (ACT) will accelerate the rate of amyloid filament formation and are major constituents of the plaques associated with AD. We now show that a dinucleotide microsatellite allele in the 5'-flanking sequence of the ACT gene, designated A10, in association with APOE*4 si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
3

Year Published

1997
1997
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 16 publications
2
13
3
Order By: Relevance
“…In contrast to that report we found only weak evidence that the AACT A10 allele was a risk factor for AD. We also found that the OR was higher in the AACT A10-group, unlike the results reported by Morgan et al (1997). In addition, we consider the`test for trend' employed in that study to be inappropriate, and we propose that these authors should have instead performed a test for interaction which would have given a non-signi®cant result (w 2 1.48, df 1, p 0.22).…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In contrast to that report we found only weak evidence that the AACT A10 allele was a risk factor for AD. We also found that the OR was higher in the AACT A10-group, unlike the results reported by Morgan et al (1997). In addition, we consider the`test for trend' employed in that study to be inappropriate, and we propose that these authors should have instead performed a test for interaction which would have given a non-signi®cant result (w 2 1.48, df 1, p 0.22).…”
Section: Discussioncontrasting
confidence: 71%
“…H to the AACT gene where the A10 allel in combination with APOE had been reported to signi®cantly increase the risk of developing AD (Morgan et al, 1997). In contrast to that report we found only weak evidence that the AACT A10 allele was a risk factor for AD.…”
Section: Discussioncontrasting
confidence: 60%
“…17 There are no significant differences in allele or genotype frequencies of the BChE-K variant between AD and control groups ( Table 2) in contrast to previous findings. 13 Allele and genotype frequencies for the PS-1 intronic polymorphism are shown in Table 3.…”
Section: Resultscontrasting
confidence: 60%
“…Although this association was con®rmed in a group of Japanese AD patients [Yoshiiwa et al, 1997], several other groups have not found this association in Caucasian AD patients Muller et al, 1996;Nacmias et al, 1996;Talbot et al, 1996;Didierjean et al, 1997;Helisalmi et al, 1997;Morgan et al, 1997;Murphy et al, 1997;Lamb et al, 1998]. Also, Muramatsu et al [1996] found a nonsigni®cant trend for the AA genotype in Japanese AD patients, which was signi®cant only in non-E4 individuals.…”
Section: Discussionmentioning
confidence: 84%